Sistema de control térmico en interiores basado en internet de las cosas con arquitectura de bajo costo - Candela Limongi, Jeniffer Andrea (2021)
The objective of this technical project is to design a prototype of the interior thermal control system based on the Internet of Things, with low-cost architecture, to optimize the operation of air conditioning systems, in addition to contribute to the problems solution for users who use the product and balance energy consumption. It began with the investigation of the different alternatives of devices and techniques of IoT (Internet of Things), to understand their operation and select the best option. Then, through a survey of a total of 385 people, it was possible to determine the acceptance that is in the market, and after that, produce a functional design of the prototype, and with this the financial analysis of the project was carried out, taking into account all possible considerations in order to obtain a favorable economic viability. In this way, a mechanism was achieved that contributes to an improvement both in the operation of air conditioning systems and in a balanced energy consumption, which in turn leads to the prolongation of the life of thermal control devices and economic savings to who buys the product.